Analysis of Liquidity, Solvency, and Profitability Ratio to Assess the Financial Performance of PT Hamparan Estate Management in 2018-2020 - Purnaningtyas, Kurnia Cahya; Utami, Hadiahti -; Zaenuddin, Achmad - (Politeknik Negeri Semarang, 2023)
Company financial performance assessment is one way for companies to evaluate both financially and company management. This is very important for the sustainability of the company in the future. Good performance is not only seen from how high the company generates profit but also from the company's ability to fulfill its obligations both short and long term. The object of this research is PT Hamparan Estate Management. This research aims to analyze the financial performance of PT Hamparan Estate Management in 2018-2020. The analytical method used is financial ratio analysis which includes liquidity ratio (current ratio & quick ratio), solvency ratio (debt to asset ratio & debt to equity ratio), and profitability ratio (ROA & ROE). The type of data used is secondary data in the form of company financial statements for 2018-2020. The results of the analysis of the company's financial performance during 2018-2020 in terms of the liquidity and solvency ratios showed good performance and tended to fluctuate from year to year, but in terms of the profitability ratios showed that the company's performance was not good and tended to decline every year. The health level of the company in terms of liquidity during 2018-2020 shows a liquid state. In terms of solvency, the company shows a solvable situation during 2018-2020. In terms of profitability during 2018-2020, it shows an unhealthy situation